Time-Lapse Tomography of A Longwall Panel: A Comparison of Location Schemes (919eac95-0539-40b5-9304-f250d4890ab6) - Kray Luxbacher (International Conference on Ground Control in Mining, 2007)
Three-dimensional time-lapse velocity tomograms were generated to image stress redistribution around a longwall panel to produce a better understanding of the mechanisms that lead to ground failure. Mining-induced microseismic events provided passive sources for the three-dimensional velocity tomography. Surface-mounted geophones monitored microseismic activity for 18 days. Most similar studies have utilized active sources including longwall shearers, controlled explosions, and hammer blows. These active sources generally require a person to initiate and measure the location and time of the source, and are not conducive to continuous monitoring. This method utilizes mining induced microseismic events as passive sources and lends itself well to continuous monitoring. Two event location methods were compared in order to move toward quantification of tomographic results in terms of ground conditions. Additionally, LAMODEL was utilized to determine the expected stress distribution around the longwall panel and compare these images to the velocity tomograms. Eighteen tomograms were generated, one per day, and high velocity regions in the set of tomograms generated from the initial location algorithm correlated with abutment stress redistribution predicted by numerical modeling. This research is significant as it has the potential to improve safety in underground mines and is the only example of long term passive velocity tomography implementation for the purpose of inferring stress redistribution around an area of active mining. Though still immature, this technology has the potential to allow mine personnel to image areas of active mining on a regular basis and detect areas with anomalous velocity distributions indicating potential safety hazards.